Analisis Kebijakan Publik Kebijakan Sosial di Perkotaan Sebagai Sebuah Kajian Implementatif - Andi Samsu Alam (Departemen Ilmu Pemerintahan Fisip Unhas, 2009)
Social problems founded both on rural and urban area in Indonesia, but the most had founded on urban area. There is more problem arise in urban than rural area. Base of it, the Urban Management have implementing as a management process to make an ideal city system as like as something was expected. The focus of urban management is closely connecting with the needs of the physical aspects, social and economic aspect of communities. The pattern of its management is highly related to the level of complexity of urban problems which related to a number of factors and challenges, such as population, high level on urbanization, Poverty increasing/minimally of employment opportunities, increasing of social inequality/economic inequality, declining of environmental quality in urban area, and ability human resources limitation, institutionally and fundrising for develop and to maintain the urban infrastructure.